Sonographic renal length in Malaysian infant population : a hospital based cross-sectional study - Aidi Aswadi Halim Lim (Kulliyyah of Medicine, International Islamic University Malaysia, 2020)
The early neonatal stage is an important period of growth and development. Organ maturity takes place at a relatively more rapid rate during this early stage of life. An insult at this stage could potentially result in physical and functional impairment of the affected organs. The kidneys are one of the organs demonstrating similar predisposition. Medical personnel have been reliant on ultrasound examination of the kidneys for years to determine various characteristics including the appropriate renal lengths. However the lack of local data means that Malaysian doctors are dependent on data from other overseas populations, which may or may not be suitable for our local infant population. Our primary aim is to determine the range of normal sonographic renal length amongst infant population up to the age of 1 year old in IIUMMC and HTAA in Kuantan, Pahang, Malaysia. We also aim to investigate any differences of the sonographic renal lengths between male and female infants in these centres. Finally we aim to propose a simple mathematical equation to enable estimation of ideal renal length based on an infant's age. All children under the age of 1 who have had ultrasound of the kidneys which were reported as normal were included in the study. Five age groups were formed based on examples from previous studies. Data were mined from the Radiology Information Systems of both centres. A total of 463 cases were selected. Two important data were obtained – an individual infant's age, their sonographic renal lengths for both kidneys as well as their gender. Their respective sonographic renal lengths were tabulated according to their respective age group, following which a group mean as well as their corresponding 95% confidence interval were derived. We derived and tabulated the means and 95% confidence intervals for both right and left kidneys separately for each individual group. We found no significant difference in the sonographic lengths of either kidneys comparing between the male and female gender. Two separate linear regression equations were formulated for the right and left kidneys respectively.We formulated a practical table of normal sonographic renal lengths according to age for infants, useful in day to day practice.